Undergraduate pharmacy students’ preference for case-based learning: a discrete choice experiment in China - Guo, Zhibo; He, Yuxing; Yan, Jianzhou (Frontiers in Pharmacology, 2025)
BackgroundUnderstanding students’ preferences is crucial for developing targeted teaching strategies and improving educational outcomes. This study aimed to investigate Chinese undergraduate pharmacy students’ preferences for case-based learning (CBL).MethodsWe conducted a discrete choice experiment (DCE) to quantify preferences for CBL. Six key attributes associated with CBL preferences were identified: case modality, provider type, group size, case authenticity, case complexity, and examination format. An online questionnaire was administered to undergraduate pharmacy students from two universities in China. The data were analyzed using a mixed logit model to estimate preference weights, assess the relative importance of the attributes, and predict uptake rates. Additionally, interaction effects and subgroup analysis were employed to identify heterogeneity in preferences among different student groups.ResultsA total of 613 participants completed the questionnaire and 482 participants were included in the analysis. The most influential attribute was case modality, with scenario simulation strongly preferred over paper modality. Case authenticity and provider type were also significant factors, followed by group size and case complexity. Examination format did not significantly affect preferences. We found heterogeneity in preferences between different groups of students. The highest uptake was achieved when cases were presented in scenario simulations by clinical instructors in small groups, using real cases of low complexity alongside the traditional written examination.ConclusionThe study highlights the importance of case modality with scenario simulation, case authenticity, and provider by clinical instructors among Chinese undergraduate pharmacy students for CBL, and suggests the need for personalized CBL approaches to accommodate different preferences.